EU Sustainability Quest: Possibilities of Consumer Sales - Selvestravičiūtė, Agnė (Teisė, 2024)
This paper analyses principal incoherence left in EU rules applicable to consumer sales against the background of the European Commission’s sustainability quest, supposedly influencing every area of the Union’s future life, and argues for a possible need for changes in contemporary consumer law in order to achieve a greater environmental good. It covers three key aspects where the Consumer Sales Directive might have done a better job in addressing environmental worries (i. e. legal guarantee term, assessment of remedies, and commercial guarantees), and states that these aspects were not modified to benefit the environment. The article then covers a deeper problem of conflicting aims that cannot be simultaneously upheld (i. e. fostering and curbing consumption at the same time), and challenges that in order to address environmental problems serious reconsiderations of consumer protection might be necessary.